Analisis Strategi Marketing Public Relations (MPR) PT Finiks Solusi Indonesia Dalam Mempertahankan Loyalitas Konsumen - Dessinta Nur Fitria; Nyoman Suardhita (Prisani Cendekia Institute, 2023)
PT. Finiks Solusi Indonesia always tries to keep consumers working with it. Therefore, within the PR Marketing division companies are required to be able to create strategies in order to maintain consumer loyalty. The purpose of this research is to analyze the marketing public relations strategy of PT. Finiks Solusi Indonesia in maintaining consumer loyalty. The author uses a descriptive qualitative research method because the data or information obtained from interviews, observations, and documentation after that the data will be managed by analyzing based on the theoretical concepts chosen by the author. According to this study's findings, the pr marketing technique of of PT. Finiks Solusi Indonesia in maintaining customer loyalty, namely providing free training or workshop, maintaining SLA and monitoring its services, providing a helpdesk container and providing a fast response. There are several supporting strategies in which the strategy has been analyzed and the results are in accordance with the three theories of pull strategy, push strategy, and pass strategy. After implementing the strategy carried out by Marketing PR, the authors use three main indicators to measure consumer loyalty who have long worked with PT. Finix Solutions Indonesia.